Annual Plan 1967-68 of the Government of Kerala - Planning Commission (Planning Commission, 1967)
This publication presents the revised estimates of expenditure under Plan schemes for the year 1966-67 and also the details of the interim Annual Plan proposed for 1967-68. IL may be recalled that the Annual Plan for 1966-67 was only an Emergency Plan. The Fourth Plan for the State was not then finalised and therefore, the Annual Plan for 1966-67 did not bear the same relationship to the State’s Fourth Plan as it would have been under normal circumstances.
Statements and Brief Description of Programme